Incidence of Overweight in Plantar Fasciitis Patients - Sakib Al Nahian, Mohammad; Alam, Md Ehsanul; Kumar Ghosh, Taposh; Nawshin, Nashid; Hafiz, Monia; Tuj Johora, Fatema; Ali, Kh Mohammad (Medicine Today, 2025)
Introduction with Objective: Plantar fasciitis is a common condition causing heel and arch pain and has been related with degenerative changes in the plantar fascia resulting in tissue thickening. The aim of this study was to assess the incidence of overweight in plantar fasciitis patients. Materials and Methods: This cross-sectional study was conducted in the Department of Physical Medicine & Rehabilitation, Dhaka Medical College Hospital, Dhaka during February 2023 to March 2024. A total of 51 patients with plantar fasciitis were included in the study. Ethical clearance was obtained from the Ethical Review Committee of Dhaka Medical College Hospital. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: The mean age of the patients was 46.6 ±4.3 years where majority of the patients (51.0%) were in 41-45 years age group and 27 (52.9%) patients were male. Among the 51 patients, 21 (41.2%) patients were homemakers whereas others were service holder (35.3%, n=18), businessmen (11.8%, n=6), and (11.8%, n=6) were involved in other professions. The mean BMI of the patients was 26.8 ±2.6 kg/m2 where 38 (74.5%) patients were overweight, while 5 (9.8%) were obese. Conclusion: Overweight is considered a significant risk factor for plantar fasciitis. Medicine Today 2025, Vol.37 (2): 244-246